Implementation of Regulations on Layoff Management and Investment at PT Sritex from the Perspective of Legal Certainty - Abdul Haris Semendawai; Muhammad Fahruddin; Emma Maripah; Sinta Elviyanti; Nisa Asqia (JURNAL ILMIAH LIVING LAW, 2026)
This study aims to analyze the implementation of regulations governing employment termination (layoffs) and investment at PT Sri Rejeki Isman Tbk (Sritex), examine the extent to which these regulations provide legal certainty for affected workers, and assess the relationship between investment conditions and mass layoffs. The study employs a normative-empirical legal research method, utilizing statutory, conceptual, and case study approaches. Data were collected through the analysis of legislation, court decisions, and academic literature, complemented by interviews with relevant stakeholders. The results indicate that implementation of layoff regulations at PT Sritex formally complied with Law Number 6 of 2023 concerning Job Creation, Government Regulation Number 35 of 2021, Government Regulation Number 37 of 2021 concerning Job Loss Insurance, and Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations. However, this implementation has not fully ensured legal certainty for workers due to regulatory disharmony between labor and bankruptcy laws, limitations in asset distribution during bankruptcy proceedings, and weaknesses in social protection mechanisms. Furthermore, declining investment performance and reduced competitiveness in the textile sector significantly contributed to the mass layoffs. The novelty of this study lies in its integrated analysis of labor and investment regulations within the framework of legal certainty in a large-scale layoff case. Unlike previous studies that focus primarily on isolated labor protection or bankruptcy issues, this research demonstrates how the interaction between investment conditions, bankruptcy proceedings, and labor regulations influences both the effectiveness of legal protection for workers and the sustainability of business activities.